Corporate governance norms and practices - Chhaochharia, Vidhi; Laeven, Luc (Journal of Financial Intermediation, 2009)
We evaluate the impact of corporate governance on the valuation of firms in a large cross-section of countries. Unlike previous work, we differentiate between minimally accepted governance attributes that are satisfied by all firms in a given country and governance attributes that are adopted at the firm level. This approach allows us to differentiate between firm-level and country-level corporate governance, thus contributing to an ongoing debate in the literature about whether governance attributes are largely determined by country factors or firm characteristics. Despite the costs associated with improving corporate governance at the firm level, we find that many firms choose to adopt governance provisions beyond those that are adopted by all firms in the country, and that these improvements in corporate governance are positively associated with firm valuation. Firms that choose not to adopt sound governance mechanisms tend to have concentrated ownership and sizeable free cash flow, consistent with agency theories based on self-interested managers and controlling shareholders. Our results indicate that the market rewards companies that are prepared to adopt governance attributes beyond those required by laws and common corporate practices in the home country.